Cryptography Reference
In-Depth Information
a pair of neighboring hybrids that are polynomial-time-distinguishable. Actually,
this holds, on the average, for a “random” pair of neighboring hybrids:
Claim 3.3.7.1: For each n satisfying Eq. (3.10),
n
1
1
n ·
Pr
D H i + n = 1 Pr
D H n = 1
1
p ( n )
·
n
i = 0
Proof: The proof is immediate by Eq. (3.10) and the definition of the hybrids. In
particular, we use the fact that H n
X n and H n
U n .
Claim 3.3.7.1 suggests a natural algorithm for predicting the next bit of
{
X n } n ∈N .
The algorithm, denoted A , selects i uniformly in
, reads i bits
from X n , and invokes D on the n -bit string that results by concatenating these i
bits with n
{
0
,
1
,...,
n
1
}
i uniformly chosen bits. If D responds with 1, then A 's prediction
is set to the value of the first among these n
i random bits; otherwise it is set
to the complementary value. The reasoning is as follows. If the first among the
n i random bits happens to equal the i + 1 bit of X n , then A is invoked on
input distributed identically to H i + n . On the other hand, if the first among the
n i random bits happens to equal the complementary value (of the i + 1 bit of
X n ), then A is invoked on input distributed identically to a distribution Z that is
even more clearly distinguishable from H i + 1
n
than is H n (i.e., H n equals Z with
2 , and H i + n otherwise). Details follow.
We start with a more precise description of algorithm A . On input 1 n
1
probability
and
x = x 1 ··· x n , algorithm A proceeds as follows:
{
,
,...,
}
1. Select i uniformly in
0
1
n
1
.
2. Select r i + 1 ,...,
r n independently and uniformly in
{
0
,
1
}
.
3. If D ( x 1 ···
x i r i + 1 ···
r n )
=
1, then output r i + 1 , and otherwise output 1
r i + 1 .
Claim 3.3.7.2: For each n satisfying Eq. (3.10),
1
2 +
1
p ( n ) · n
[ A (1 n
Pr
,
X n )
=
next A ( X n )]
Proof: Let us denote by X j
,..., R n a sequence
of n i independent random variables each uniformly distributed over { 0 , 1 } .
Using the definition of A and the fact that
the j th bit of X n , and by R i + 1
Pr
[ X i + 1
= R i + 1 ] =
1
2 ,wehave
s A ( n ) def
[ A (1 n
= Pr
,
X n )
=
next A ( X n )]
n
1
1
n ·
Pr
[ D ( X 1
··· X i R i + 1
··· R n ) = 1& R i + 1
= X i + 1 ]
=
(
i = 0
+ Pr
[ D ( X 1
··· X i R i + 1
··· R n ) = 0&1 R i + 1
= X i + 1 ])
n 1
1
2 n ·
[ D ( X 1
X i X i + 1 R i + 2
R n )
=
(
Pr
···
···
=
1]
i = 0
X i X i + 1 R i + 2
[ D ( X 1
R n )
+
1
Pr
···
···
=
1])
Search WWH ::




Custom Search